2010
DOI: 10.1021/la904431z
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly and Dual-Stimuli Sensitivities of Hydroxypropylcellulose-graft-poly(N,N-dimethyl aminoethyl methacrylate) Copolymers in Aqueous Solution

Abstract: The self-assembly and pH- and thermo-sensitivities properties of hydroxypropyl cellulose-graft-poly(N,N-dimethyl aminoethyl methacrylate) (HPC-g-PDMAEMA) copolymers in aqueous solutions were investigated by transmittance, dynamic light scattering (DLS), and (1)H NMR spectroscopy. Micelles with different structure can be formed by varying either pH value or temperature. At low pH, e.g., 3.0, the HPC backbone of the copolymer collapse to form the core of micelles stabilized with protonated PDMAEMA side chains on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 70 publications
0
72
0
2
Order By: Relevance
“…Turbidity measurement is a common technique for estimating the LCST of the thermo-responsive polymers in aqueous solutions [6,9,33]. The PDMAEMA-b-PAA is a typical diblock polyampholyte with both thermal-and pH-responsive sensitivities because the PDMAEMA block is thermal-responsive and both AA and DMAEMA monomers are weak electrolytes.…”
Section: Lcst Of the Polyampholyte Pdmaema-b-paamentioning
confidence: 99%
See 2 more Smart Citations
“…Turbidity measurement is a common technique for estimating the LCST of the thermo-responsive polymers in aqueous solutions [6,9,33]. The PDMAEMA-b-PAA is a typical diblock polyampholyte with both thermal-and pH-responsive sensitivities because the PDMAEMA block is thermal-responsive and both AA and DMAEMA monomers are weak electrolytes.…”
Section: Lcst Of the Polyampholyte Pdmaema-b-paamentioning
confidence: 99%
“…Patrickios and co-workers [34] found that the cloud point of PDMAEMA stars in pure water does not rely much on the arm number. Ma et al [9] studied the thermo-responsive properties of hydroxypropyl cellulose-graft-poly(N,N-dimethyl aminoethyl methacrylate) (HPC-g-PDMAEMA) at different pHs and found that the LCST of HPC-g-PDMAEMA was dramatically varied on the solution pH. In this work, the aim is to research how the LCST varies with solution concentration and pH in the PDMA-EMA-b-PAA with different thermal-segment lengths.…”
Section: Lcst Of the Polyampholyte Pdmaema-b-paamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, HPC has a lower critical solution temperature (LCST, *41°C) in water. Heating a dilute HPC water solution to temperatures only a couple of degrees higher than the LCST can lead to metastable nanosphere aggregates instead of precipitation (Gao et al 2001), which means that HPC can demonstrate a corresponding phase change when controlling the water solution temperature (Ma et al 2010b). To the best of our knowledge, the effects of the use of temperature-responsive HPC as a matrix and the corresponding effect of its phase change on the mechanical properties of CNCs/HPC nanocomposites has never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al reported a pH-responsive POSS end-capped polymer, POSS-PDMAEMA, and studied the self-assembly behaviour of POSS-PDMAEMA in aqueous solution [19]. PDMAEMA is a weak cationic polyelectrolyte that is water soluble and sensitive to pH [20][21][22][23][24][25]. Polymethyl methacrylate (PMMA) is hydrophobic and widely used to form copolymer with hydrophilic polymer.…”
Section: Introductionmentioning
confidence: 99%